Paying for Protection: The Effects of Having an Elite Left Tackle - Quinn Andrew Wesley Keefer (Journal of Applied Sports Management, 2017)
We exploit relatively new data collected by the NFL, since 2009, on the number of hits taken by a team’s quarterback to estimate the benefits and costs of employing an elite left tackle. We model the effect of an elite left tackle using a system of equations, which is estimated with seemingly unrelated regressions. Our system of equations considers quarterback hits, yards gained, and the probability of a quarterback injury. Overall, an All-Pro left tackle increases offensive production by 106 yards, or 8.5 points, and reduces the probability a team’s quarterback misses a game due to injury by 10.3 percentage points. However, the estimated compensation premium for elite left tackles is $1,151,000 to $1,528,000. Furthermore, the cost of an elite left tackle is far greater than the cost associated with an equal increase in points scored acquired through the running back market. Taken together; our results suggest elite left tackles are valued far above their expected contribution to offensive production due to the very large reduction in quarterback injury risk.
Keywords: Left tackle; quarterback protection; points scored; compensation premium